More biofuel = more food? - Niklas Hinkel (Institute of Energy Economics at the University of Cologne (EWI), 2022)
In face of increased efforts to mitigate climate change, biofuels may be included in reduction plans forgreenhouse gas emissions. Feedstock for first generation biofuels and food crops both use arable land andmay compete for it. Also, fuel is an input for the production and transport of food. The purpose of thispaper is to quantify with empirical data how these two aspects affect market outcomes and to introduce acounterfactual setting where the latter aspect dominates the former. The setting allows an expansion ofbiofuel production to increase food production by lowering costs of production and transport. Namely,lower costs increase market access, allowing a higher utilization of idle production capacities for foodcrops. For this quantification, I develop an open market, welfare maximizing, partial equilibrium modelfor three interdependent goods fuel, fuel feedstock, and food (these goods are represented by diesel/biodiesel,palm oil, and cassava/maize respectively). The model is calibrated to Zambia, which exhibits the necessaryunderlying conditions of underutilized agricultural capacity, high transport costs, and low exports offood. Compared to a baseline, model results show the counterfactual switch from fossil diesel to biodieselto reduce the diesel price by51%. This increases food supply (cassava and maize combined) by0.4%and decreases related prices by3%. Overall welfare increases by9.9%. If additionally, a higher worldmarket price of maize renders exports just profitable, overall welfare continues to gain9.9%, domesticfood supply rises by0.3%, and related prices drop by2%, but food supply including exports grows by32%. Furthermore, the introduction of a palm oil based biodiesel sector eliminates import dependency onfossil diesel and palm oil.
Keywords: C61; O13; O55; Q16; Q18; 330; Biofuel; Land Use; Energy Economics; Partial Equilibrium Model; Zamb